2021
DOI: 10.3389/fimmu.2021.794593
|View full text |Cite
|
Sign up to set email alerts
|

Gill Transcriptomic Responses to Toxin-producing Alga Prymnesium parvum in Rainbow Trout

Abstract: The gill of teleost fish is a multifunctional organ involved in many physiological processes, including protection of the mucosal gill surface against pathogens and other environmental antigens by the gill-associated lymphoid tissue (GIALT). Climate change associated phenomena, such as increasing frequency and magnitude of harmful algal blooms (HABs) put extra strain on gill function, contributing to enhanced fish mortality and fish kills. However, the molecular basis of the HAB-induced gill injury remains lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…The chemical composition of the toxins of P. parvum, collectively referred to as prymnesins, has been found to contain biomolecules like glycolipids, galactolipids, proteolipids, and lipid-carbohydrate molecules [36], and the way they elicit toxicity are being investigated. Clinton et al examined the gill transcriptome sensitivity of juvenile rainbow trout as a function of toxin dosage and fish phenotype [39]. Typically, the fish were exposed to prymnesins for 4-5 h. The study demonstrated the activation of acute pro-inflammatory cytokines that cause severe gill malfunction after exposure to the toxins, and these responses are independent of toxin dosage and fish phenotype.…”
Section: Prymnesium Parvummentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of the toxins of P. parvum, collectively referred to as prymnesins, has been found to contain biomolecules like glycolipids, galactolipids, proteolipids, and lipid-carbohydrate molecules [36], and the way they elicit toxicity are being investigated. Clinton et al examined the gill transcriptome sensitivity of juvenile rainbow trout as a function of toxin dosage and fish phenotype [39]. Typically, the fish were exposed to prymnesins for 4-5 h. The study demonstrated the activation of acute pro-inflammatory cytokines that cause severe gill malfunction after exposure to the toxins, and these responses are independent of toxin dosage and fish phenotype.…”
Section: Prymnesium Parvummentioning
confidence: 99%
“…Typically, the fish were exposed to prymnesins for 4-5 h. The study demonstrated the activation of acute pro-inflammatory cytokines that cause severe gill malfunction after exposure to the toxins, and these responses are independent of toxin dosage and fish phenotype. P. parvum excretes toxins to catch prey; however, it is hypothesized that Prymnesium toxins are released again after cell-to-cell contact in a process known as "toxinmediated micropredation" [39,40]. In fact, reports of direct physical contact with animals have been reported [41].…”
Section: Prymnesium Parvummentioning
confidence: 99%